China in the Middle East: Priorities and Strategic Characteristics - Sherwan Abdulrahman Mohammed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
This study aims to identify China's strategic priorities and key directions of China's political presence، which seeks to balance threats and opportunities in a volatile region such as the Middle East. Given the instability in the area caused by the U.S.'s global war on terror, the specifics of China's policy in the Middle East and North Africa are noteworthy, given that China's interests are at stake. Therefore، using analytical methods، the factors influencing the policy in the Middle East of the People's Republic of China were identified، which undoubtedly contributed to the change in the regional order. Finally, this study concludes that the future of China's presence in the Middle East will be determined by China's global strategy، as well as China's vision of its role and the future world order in general.